FINANCIAL STATEMENT ANALYSIS PT. TELEKOMUNIKASI INDONESIA (PERSERO) TBK AND PT. XL AXIATA TBK PERIOD 2021-2022 - Eko Agus Setiawan; Muhammad Mubariz; Rahmawati; Sri Hermuningsih (ZILLZELL MEDIA PRIMA, 2023)
The research conducted aims to analyze the comparison of financial performance in telecommunications companies listed on the IDX using the companies PT Telkom Indonesia Tbk. and PT XL Axiata Tbk. in the period 2021 and 2022. In this study the method used is comparative research. The results of the study indicate that there are several financial performances that show differences between PT Telekomunikasi Indonesia (Persero) Tbk. And PT. XL Axiata Tbk.. From the ratio analysis conducted on PT Telkomunikasi Indonesia Tbk and PT XL Axiata Tbk in 2021-2022, it shows that PT Telkomunikasi Indonesia Tbk is always in a better condition than PT XL Axiata Tbk, especially in the liquidity ratio, debt ratio, and profitability. better than PT XL Axiata Tbk, especially in the liquidity ratio, debt ratio, and profitability ratio, this indicates that the performance of PT. Telekomunikasi Indonesia Tbk is better and more stable when compared to Pt. Xl axiata Tbk is only superior in the activity ratio.